Pengetahuan KriyÄ Yoga Sebagai Upaya Peningkatan Kesadaran Rohani - Brahman, I Made Adi (Institut Hindu Dharma Negeri Denpasar, 2021)
Homo religios is a human dimension that tries to find the meaning of life in the spiritual dimension. The effort to uncover the veil of the truth of life in the spiritual dimension is through an activity called yoga. KriyÃ yoga is a part of yoga that places more emphasis on controlling the flow of life force (prana) through a series of specific pranayama techniques to achieve union with cosmic consciousness (God). In learning kriyÃ yoga techniques, one should attend to a competent teacher in a devotional manner. A series of kriyÃ yoga techniques that emphasize certain pranayama techniques are used to cleanse and provide a maximum flow of life energy (prana) to the energy centers (chakras) and the brain contained in humans. When this flow of prana flows more and more to the spiritual organ it automatically promotes an increase in awareness in a yogi.